γ-decay of resonance-like structure observed in ³⁰Si(p,γ)³¹p reaction - Kachan, A.S.; Vodin, A.N.; Korda, V.Yu.; Korda, L.P.; Mishchenko, V.M.; Slabospitsky, R.P. (Вопросы атомной науки и техники, 2002)
γ-Decay of a resonance-like structure observed in the reaction ³⁰Si(p,γ)³¹p in the energy region Ep=1.4-2.7 MeV of accelerated protons is studied. The M1 resonance built on the ground state of ³¹P is identified. The position of the M1 resonance is explained taking into account pairing forces.